2017
DOI: 10.3791/56159
|View full text |Cite
|
Sign up to set email alerts
|

Sample Extraction and Simultaneous Chromatographic Quantitation of Doxorubicin and Mitomycin C Following Drug Combination Delivery in Nanoparticles to Tumor-bearing Mice

Abstract: Combination chemotherapy is frequently used in the clinic for cancer treatment; however, associated adverse effects to normal tissue may limit its therapeutic benefit. Nanoparticle-based drug combination has been shown to mitigate the problems encountered by free drug combination therapy. Our previous studies have shown that the combination of two anticancer drugs, doxorubicin (DOX) and mitomycin C (MMC), produced a synergistic effect against both murine and human breast cancer cells in vitro. DOX and MMC co-l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…However, the clinical combination of DOX and MMC (DOX-MMC) was halted owing to its severe cardiotoxicity to cancer patients [62,63] . We perceived that this off-target adverse effect could be reduced with optimal scheduling and dosing of the two drugs by rationally designing a drug nanocarrier system [64][65][66][67][68] .…”
Section: Integration Of Nanotechnology With Pharmacology For Enhancedmentioning
confidence: 99%
“…However, the clinical combination of DOX and MMC (DOX-MMC) was halted owing to its severe cardiotoxicity to cancer patients [62,63] . We perceived that this off-target adverse effect could be reduced with optimal scheduling and dosing of the two drugs by rationally designing a drug nanocarrier system [64][65][66][67][68] .…”
Section: Integration Of Nanotechnology With Pharmacology For Enhancedmentioning
confidence: 99%
“…78,79 To maximize the benefit of such drug combinations, nanocarrier systems were designed that circumvented off-target toxicity through tumor-specific release of drugs. 49,50,56,57,80 The synergistic anticancer effect of DOX− MMC combination therapy has been investigated in multiple murine and human breast cancer cell lines and tumor models. 49,50 circulation of both DOX and MMC (Figure 2a) and enabled ratio-metric codelivery of DOX and MMC in breast tumors (Figure 2b).…”
Section: Synergistic Drug Combination Nanomedicine For Enhancing Chem...mentioning
confidence: 99%
“…This effect, together with glutathione depletion by MMC and formaldehyde formation from MMC enhanced DOX-induced DNA DSBs, demonstrating the synergistic interactions of DOX–MMC combination . However, severe cardiotoxicity has limited the clinical translation of DOX and MMC (DOX–MMC) combinations to cancer patients. , To maximize the benefit of such drug combinations, nanocarrier systems were designed that circumvented off-target toxicity through tumor-specific release of drugs. ,,,, The synergistic anticancer effect of DOX–MMC combination therapy has been investigated in multiple murine and human breast cancer cell lines and tumor models. , A DOX to MMC molar ratio of 2:1 was used in a PLN (DMPLN) formulation. DMPLN prolonged plasma circulation of both DOX and MMC (Figure a) and enabled ratio-metric codelivery of DOX and MMC in breast tumors (Figure b). , The DMPLN also exhibited enhanced tumor apoptosis and extended host-survival in both human and murine MDR tumor models compared to free DOX–MMC solution and liposomal DOX (DOXIL) (Figure c,d). , Importantly, DMPLN formulations did not cause detectable cardiotoxicity in the animals, in contrast to free DOX–MMC (Figure e).…”
Section: Synergistic Drug Combination Nanomedicine For Enhancing Chem...mentioning
confidence: 99%
“…Doxorubicin (DOX) is commonly the first‐line chemotherapeutic agent for many solid tumours and is highly effective in oxygenated regions of the tumour and mitomycin C (MC) is another chemotherapic compound which reveals cytotoxicity against non‐proliferating cells in hypoxic tumour regions via enhanced bioreductive activation. Considering systematic in vitro studies on free drug combinations, it was revealed that DOX and MC can produce synergistic cytotoxicity in breast cancer cells when applying together [15].…”
Section: Introductionmentioning
confidence: 99%